2017
DOI: 10.1504/ijsurfse.2017.088120
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the tribological behaviour of electrocodeposited Ni-MoS<SUB align="right">2 composite coatings

Abstract: Objective. To discuss a patient with a prenatal diagnosis of unilateral isolated femoral focal deficiency. Case. Antenatal diagnosis of unilateral isolated femoral focal deficiency was made at 20 weeks of gestation. The length of left femur was shorter than the right, and fetal femur length was below the fifth percentile. Proximal femoral focal deficiency was diagnosed. After delivery, the diagnosis was confirmed with skeletal radiographs and magnetic resonance imaging. In prenatal ultrasonographic examination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…Nickel-based composite coatings with embedded MoS2 particles have been developed to reduce friction and wear for critical mechanical components in advanced automobile and aerospace applications [4][5][6][7][8][9]. The addition of MoS2 particles can modify the microstructure, internal stress, composition and wear behaviour of the coatings, many of them showing lower friction against steel and improved wear resistance compared to coatings without particles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel-based composite coatings with embedded MoS2 particles have been developed to reduce friction and wear for critical mechanical components in advanced automobile and aerospace applications [4][5][6][7][8][9]. The addition of MoS2 particles can modify the microstructure, internal stress, composition and wear behaviour of the coatings, many of them showing lower friction against steel and improved wear resistance compared to coatings without particles.…”
Section: Introductionmentioning
confidence: 99%
“…Particle concentration and degree of dispersion in the electrolyte are major factors. A wide range of particle concentrations in the bath has been reported, as shown in Table 1, some using lower concentrations of 1 -2 g dm -3 [5,7,9] and others higher concentrations of up to 30 g dm -3 [4,6,8]. The optimum particle concentration in the bath may vary depending on the deposition conditions but it should be kept as low as possible in order to control the running and bath inventory costs.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous embeddable particles, MoS 2 with layered structure is an ideal solid lubricant for the preparation of coatings with excellent friction and wear resistance 15 . The introduction of solid lubricant can obviously improve the wear resistance of the material, thus prolonging the service life of the material [16][17][18] . Furthermore, Ni-Co matrix has aroused growing interest due to its exceptional comprehensive properties [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%
“…Among the researchers who have worked on Ni-MoS 2 coatings [22][23][24][25][26][27][28][29], Chang et al [24] have studied co-deposition of Ni-MoS 2 composite coatings by rotating disc electrode technique. They reported that bath temperature and concentration of MoS 2 particles affected weight percentage of MoS 2 in the coatings.…”
Section: Introductionmentioning
confidence: 99%
“…They have reported that these coatings have good tribological behaviour in these atmospheres and adding MoS 2 and graphite together showed good synergistic effects. Guler et al [29] worked on Ni-MoS 2 composite coatings by electroplating and investigated the effects of pH, surfactant concentration and other electroplating parameters on tribological behaviour of these coatings. They have reported that the coefficient of friction (COF) decreased with increasing the amount of MoS 2 particles incorporation in the coatings and decreasing particle size.…”
Section: Introductionmentioning
confidence: 99%